IMPROVEMENT, DEVELOPMENT AND PRACTICAL APPLICATION OF VARIOUS MARKETING TECHNOLOGIES AND INSTRUMENTS TO PROMOTE FOLK CRAFTS - R. Gavva; E. Lozhkomoeva; T. Nechaeva (Вестник университета, 2017)
Folk handicrafts are a historically developed kind of handicraft activity, products of which are products made from simple improvised materials with the help of simple tools. For the majority of folk crafts, the creative orientation of this activity and the high artistic level of the products are characteristic. Developed in Russia in the XVII-XIX centuries, national crafts were irretrievably lost in the middle of the twentieth century and again began to revive only in recent years. The article discusses the actual problems of the revival of Russian folk crafts and the application of classical marketing techniques to their promotion. The possibilities of applying new marketing technologies to the promotion of the goods of folk art, as well as the prospects of educational activity in these areas are analyzed.